2002
DOI: 10.1063/1.1493794
|View full text |Cite
|
Sign up to set email alerts
|

Three-halves harmonic emission from femtosecond laser produced plasmas

Abstract: Measurements of three-halves harmonic radiation (3 0 /2) produced by femtosecond, Ti:sapphire laser pulses (р2ϫ10 17 W/cm 2 ) in long density scale length plasmas generated from solid aluminum targets are presented. The 3 0 /2 emission yield shows excellent agreement with theories of the two-plasmon decay instability in the predominantly linear regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The intensity of the light beam emitted in the 125° direction is almost double of that of the light beam emitted in the direction of 45°, while this later is narrower. This result is globally in agreement with some experimental results [12,16,17,19,20] , which in particular have demonstrated the existence of the twobeam structure for the References [12,20] have reported an angle of about 65°-70° for the forward beam and an angle of about 110°-120° for the backward beam, while reference [17] has obtained the maximum forward at 37° and the backward maximum at 153°, with respect to the laser incidence. They also have found that the angular distribution is also subject to the variation of the experimental parameters such as pulse-prepulse time delay and plasma scale length.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The intensity of the light beam emitted in the 125° direction is almost double of that of the light beam emitted in the direction of 45°, while this later is narrower. This result is globally in agreement with some experimental results [12,16,17,19,20] , which in particular have demonstrated the existence of the twobeam structure for the References [12,20] have reported an angle of about 65°-70° for the forward beam and an angle of about 110°-120° for the backward beam, while reference [17] has obtained the maximum forward at 37° and the backward maximum at 153°, with respect to the laser incidence. They also have found that the angular distribution is also subject to the variation of the experimental parameters such as pulse-prepulse time delay and plasma scale length.…”
Section: Resultssupporting
confidence: 81%
“…The backward beam of the 2 0 emission has been reported by several experimental works, but, to the best of our knowledge, its forward beam has not been measured or reported before. Its disappearance in the measured spectrum is may be caused by the spatial effects, as reference [20] has pointed out. Conversion efficiency of the order of 6×10 −4 was obtained for the 2 0 emission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations